THE IMPACT OF DAIRY CONSUMPTION ON WEIGHT FLUCTUATIONS AND OBESITY RISK THROUGHOUT MENOPAUSE: A COMPREHENSIVE SYSTEMATIC REVIEW - Fitriana, Ilma; Intan Permatasari, Dela (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Introduction: The perimenopausal transition poses significant physiological changes and an elevated risk of obesity among women, with studies demonstrating weight gain and metabolic disruptions during this phase. Dairy products, recommended in the typical diet, remain contentious in their impact on weight despite their nutrient-rich composition. Our systematic review aims to address this uncertainty by synthesizing existing evidence on the association between dairy consumption, weight change, and obesity risk during the menopausal transition, shedding light on the nuanced effects of different dairy products and informing tailored dietary interventions for optimal health during this critical life stage. Method: The researchers in this study followed the 2020 Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines to ensure that their work met the required standards. This was done to ensure the precision and reliability of the conclusions derived from the research. Result: This systematic review investigated final 20 articles. After looking at the titles and summaries, we found 10 papers that fit our criteria. At first, we excluded several articles because they were written in review style and case reports. But after reading the full papers carefully, we included five papers in our final analysis. These papers included analytical cohort, randomized, crossover study, and prospective study. Conclusion: In conclusion, incorporating yogurt into the diet may benefit perimenopausal women by reducing weight gain and obesity risk, but further investigation is needed to understand the underlying mechanisms. Additionally, controlled-feeding studies showed limited effects of short-term consumption of 2 fat milk on cardiometabolic risk factors in postmenopausal women with abdominal obesity, raising questions about disparities with epidemiological findings associating dairy consumption with reduced risk of metabolic disorders. Longitudinal cohort studies found no evidence supporting the beneficial effects of dairy intake on bone health in middle-aged women, while higher total dairy intake, mainly from high-fat sources, was associated with less weight gain over time in women with normal BMI at baseline. Further well-powered trials are needed to comprehensively understand dairy's role in preventing weight gain and obesity across different life stages.